Prevalence of and Factors Associated With Depressive Symptoms Among College Students in Wuhan, China During the Normalization Stage of COVID-19 Prevention and Control - Yu, Jincong; Yang, Ziyun; Wu, Yuqin; Ge, Ming; Tang, Xuemei; Jiang, Hongbo (Frontiers in Psychiatry, 2021)
Objectives: The 2019 coronavirus disease (COVID-19) epidemic has led to persistent negative psychological effects on the general public, especially on college students, who are highly susceptible to psychological difficulties such as fear, anxiety and depression. Little information is known about depressive symptoms among college students during the normalization stage of COVID-19 prevention and control in China. This study aimed to understand the prevalence of and factors associated with depressive symptoms after a long quarantine time and online learning at home among college students in Wuhan, China. Materials and Methods: A web-based survey was conducted from July to August 2020 during the Chinese summer holiday to collect data on sociodemographic variables, depressive symptoms and their potential associated factors using an electronic questionnaire among college students in Wuhan, China. The Patient Health Questionnaire-9 (PHQ-9) was used to measure depressive symptoms. Binary logistic regression was used to explore the factors associated with depressive symptoms. Results: A total of 9383 college students were included in the analysis. The prevalence of depressive symptoms was 15.8% (1485/9383) among college students. The binary logistic regression showed that the experience of being quarantined for observation or treatment, family members or friends dying of COVID-19, rarely or never seeking help from others, fewer supportive relatives or friends, less support from family in the past month, a worse relationship with parents at home, a longer time spent daily on electronic devices except for online learning, and feeling anxious in the face of returning to school were independently associated with a higher risk of depressive symptoms. Academic stress and concern about the epidemic were the main reasons for their anxiety. Conclusions: Targeted psychological intervention measures are recommended for college students to improve their mental health during the normalization stage of COVID-19 prevention and control.